Root length of aquatic plant, Lemna minor L., as an optimal toxicity endpoint for biomonitoring of mining effluents. (October 2014) - Gopalapillai, Yamini; Vigneault, Bernard; Hale, Beverley A
ABSTRACT Lemna minor, a free‐floating macrophyte, is used for biomonitoring of mine effluent quality under the Metal Mining Effluent Regulations (MMER) of the Environmental Effects Monitoring (EEM) program in Canada and is known to be sensitive to trace metals commonly discharged in mine effluents such as Ni. Environment Canada's standard toxicity testing protocol recommends frond count (FC) and dry weight (DW) as the 2 required toxicity endpoints—this is similar to other major protocols such as those by the US Environmental Protection Agency (USEPA) and the Organisation for Economic Co‐operation and Development (OECD)—that both require frond growth or biomass endpoints. However, we suggest that similar to terrestrial plants, average root length (RL) of aquatic plants will be an optimal and relevant endpoint. As expected, results demonstrate that RL is the ideal endpoint based on the 3 criteria: accuracy (i.e., toxicological sensitivity to contaminant), precision (i.e., lowest variance), and ecological relevance (metal mining effluents). Roots are known to play a major role in nutrient uptake in conditions of low nutrient conditions—thus having ecological relevance to freshwater from mining regions. Root length was the most sensitive and precise endpoint in this study where water chemistry varied greatly (pH and varying concentrations of Ca, Mg, Na, K, dissolved organic carbon, and an anthropogenic organic contaminant, sodium isopropyl xanthates) to match mining effluent ranges. Although frond count was a close second, dry weight proved to be an unreliable endpoint. We conclude that toxicity testing for the floating macrophyte should require average RL measurement as a primary endpoint. Integr Environ Assess Manag 2014;10:493–497. © 2014 SETAC